Effect of Boiler Chimney Design on Particulate Emission Dispersion Using Aermod Modelling - Prabasari, Ira Galih; Hutagalung, Winny Laura Christina; Bahar, Fetty Febriasti; Kumalasari, Dyah (Rekayasa, 2025)
In the power plants operation, the combustion process will produce particulate emissions. Particulate emissions themselves are known have a negative impact on health, such as causing respiratory problems. The pattern of particulate emissions from boiler chimneys needs to be studied to minimize the spread of pollution to the environment. The particulate emission dispersion model generated from the chimney of a boiler can be known using the aermod modeling tool, through this model, the concentration of particulate emissions received by the environment around the activity can be studied. The design of the boiler chimney is also known to affect the concentration of particulate matter that is dispersed. This study aims to determine the effect of chimney design on the distribution of particulate emissions from boilers. The particulate dispersion model was carried out using the aermod modeling tool with the independent variables were variations in chimney heights of 21 meters and 25 meters. From the dispersion analysis, it can be seen that the 21-meter chimney results in higher emission concentrations at close range because the lower chimney causes less optimal dispersion and tends to have a more significant local impact due to higher emission concentrations near the source. The 25-meter chimney provides better dispersion results more effective in dispersing pollutants over a wider area. The result of this research is consistent with plume rise theory and the Gaussian dispersion model, which states that the higher the stack, the more potential for the released flue gas and particulates to disperse vertically and horizontally before reaching ground level. Taller chimneys allow emissions to be released at a higher altitude, which can reduce particulate concentrations in the area around the plant or industrial installation. As the stack height increases, emissions are dispersed more widely in the atmosphere, so the potential for pollutant accumulation in areas near the source is reduced